Unipolar electrogram‐based voltage mapping with far‐field cancellation to improve detection of abnormal atrial substrate during atrial fibrillation. (19th March 2021) - Ragot, Don; Nayyar, Sachin; Massin, Sophia Z.; Ha, Andrew C. T.; Singh, Sheldon M.; Labos, Christopher; Suszko, Adrian; Dalvi, Rupin; Chauhan, Vijay S.
Abstract: Introduction: An important substrate for atrial fibrillation (AF) is fibrotic atrial myopathy. Identifying low voltage, myopathic regions during AF using traditional bipolar voltage mapping is limited by the directional dependency of wave propagation. Our objective was to evaluate directionally independent unipolar voltage mapping, but with far‐field cancellation, to identify low‐voltage regions during AF. Methods: In 12 patients undergoing pulmonary vein isolation for AF, high‐resolution voltage mapping was performed in the left atrium during sinus rhythm and AF using a roving 20‐pole circular catheter. Bipolar electrograms (EGMs) (Bi) < 0.5 mV in sinus rhythm identified low‐voltage regions. During AF, bipolar voltage and unipolar voltage maps were created, the latter with (uni‐res) and without (uni‐orig) far‐field cancellation using a novel, validated least‐squares algorithm. Results: Uni‐res voltage was ~25% lower than uni‐orig for both low voltage and normal atrial regions. Far‐field EGM had a dominant frequency (DF) of 4.5–6.0 Hz, and its removal resulted in a lower DF for uni‐orig compared with uni‐res (5.1 ± 1.5 vs. 4.8 ± 1.5 Hz; p  < .001). Compared with Bi, uni‐res had a significantly greater area under the receiver operator curve (0.80 vs. 0.77; p  < .05), specificity (86% vs. 76%; p  < .001), and positive predictive value (43% vs. 30%; p  < .001) for detecting low‐voltage during AF. Similar improvements in specificity and positive predictive value were evident for uni‐res versus uni‐orig. Conclusion: Far‐field EGM can be reliably removed from uni‐orig using our novel, least‐squares algorithm. Compared with Bi and uni‐orig, uni‐res is more accurate in detecting low‐voltage regions during AF. This approach may improve substrate mapping and ablation during AF, and merits further study.